2021
DOI: 10.1557/s43578-021-00155-z
|View full text |Cite
|
Sign up to set email alerts
|

Single- or double A-site cations in A3Bi2I9 bismuth perovskites: What is the suitable choice?

Abstract: Investigations on the effect of single or double A-site cation engineering on the photovoltaic performance of bismuth perovskite-inspired materials (A3Bi2I9) are rare. Herein, we report novel single- and double-cation based bismuth perovskite-inspired materials developed by (1) completely replacing CH3NH3+ (methylammonium, MA+) in MA3Bi2I9 with various organic cations such as CH(NH2)2+ (formamidinium, FA+), (CH3)2NH2+ (dimethylammonium, DMA+), C(NH2)3+ (guanidinium, GA+) and inorganic cations such as cesium (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Figure 9 c shows that the K-2 device preserved over 98% of its original PCE after 90 days, suggesting potentially improved stability. Based on these findings, it is clear that the KI-incorporated Cs 3 Bi 2 I 9 device is superior to its counterparts [ 33 , 66 , 68 ]. To that end, if it can achieve a performance on par with a Cs 3 Bi 2 I 9 -based perovskite device, it could be a viable alternative to a Pb-based perovskite device in addressing toxicity and instability.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9 c shows that the K-2 device preserved over 98% of its original PCE after 90 days, suggesting potentially improved stability. Based on these findings, it is clear that the KI-incorporated Cs 3 Bi 2 I 9 device is superior to its counterparts [ 33 , 66 , 68 ]. To that end, if it can achieve a performance on par with a Cs 3 Bi 2 I 9 -based perovskite device, it could be a viable alternative to a Pb-based perovskite device in addressing toxicity and instability.…”
Section: Resultsmentioning
confidence: 99%
“…Research efforts have been made to enhance the device performance by optimizing the fabrication method, precursor, and additive engineering. 144,311–313 Though the highest PCE of 3.2% has been achieved for Cs 3 Bi 2 I 9 cells, 314 the rest of the reports have shown PCEs below 1%. 307 As the wide bandgap of A 3 Bi 2 X 9 was considered to be one of the factors that limit the performance, attempts have been made to decrease the bandgap.…”
Section: Bismuth Perovskite (Analog) Solar Cellsmentioning
confidence: 98%
“…In the literature it was shown that A 3 Bi/Sb 2 I 9 derivatives treated as OD-type perovskites adopt discrete bioctahedral units. [32][33][34][35][36][37] The anionic component is discrete and built of face-sharing bioctahedra [M 2 I 9 ] 3− , whereas pyrazolium cations exhibit distinct dynamical disorder. The room temperature structure (II) is orthorhombic, with a Cmcm space group.…”
Section: Dalton Transactions Papermentioning
confidence: 99%